2014
DOI: 10.1021/ml500128g
|View full text |Cite
|
Sign up to set email alerts
|

Novel FTY720-Based Compounds Stimulate Neurotrophin Expression and Phosphatase Activity in Dopaminergic Cells

Abstract: α-Synuclein is a chaperone-like protein implicated in Parkinson's disease (PD). Among α-synuclein's normal functions is an ability to bind to and stimulate the activity of the protein phosphatase 2A (PP2A) catalytic subunit in vitro and in vivo. PP2A activity is impaired in PD and in dementia with Lewy Bodies in brain regions harboring α-synuclein aggregates. Using PP2A as the readout, we measured PP2A activity in response to α-synuclein, ceramides, and FTY720, and then on the basis of those results, we create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…These indings suggest that FTY720 holds promise as a PD therapeutic acting, at least in part, through AKT/ERK1/2/P-CREBassociated BDNF expression. [7,8]. Together, these data strongly suggest that FTY720 is highly protective in vivo.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…These indings suggest that FTY720 holds promise as a PD therapeutic acting, at least in part, through AKT/ERK1/2/P-CREBassociated BDNF expression. [7,8]. Together, these data strongly suggest that FTY720 is highly protective in vivo.…”
Section: Introductionmentioning
confidence: 75%
“…Previous studies have shown that FTY720 can increase BDNF expression in dopaminergic MN9D cells [7]. In order to assess whether it also increased BDNF expression in another dopaminergic cell line, we next treated SH-SY5Y cells with 2 μM of FTY720 at various time points (4, 8 and 24 h) then measured BDNF protein levels.…”
Section: Fty720 Promotes Phosphorylation Of Pro-survival Molecules Amentioning
confidence: 99%
“…Previously we and others have studied protection by FTY720, an approved oral immunosuppressive drug for multiple sclerosis, that when phosphorylated acts on sphingosine-1-phosphate receptors (S1P-Rs) [25]. FTY720 causes immunosuppression but also enhances expression of brain derived trophic factor in multiple cell and animal models [26][27][28][29][30]. We showed that FTY720 improves GI physiology/function and reduces GI aSyn pathology in A53T Tg parkinsonian mice [22].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, evidence has been obtained showing that the therapeutic effect of FTY‐720 in RRMS is due to its ability to affect both the immune system and CNS (Zhang et al, ). Many researches have proposed that FTY‐720 can exert a neuroprotective effect in several CNS disorders, such as stroke, Alzheimer's disease and Parkinson's disease (Hemmati et al, ; Vargas‐Medrano et al, ).…”
Section: Introductionmentioning
confidence: 99%